Determinants of Investor Demand on Issuance of Sukuk Sr-014 - Ferdy Imanzah; Indah Juliana (Universitas Muhammadiyah Surabaya, 2023)
AbstractThe covid-19 pandemic has not ended, so many people save their funds in various low risk instruments with high returns. Retail Sukuk as an instrument with sharia principles have high returns and low risk levels because they are issued by the state and guaranteed by the state. Retail Sukuk or SR are securities with sharia principles owned by individuals specifically for Indonesian citizens and purchased through a selling agent appointed by the order as the issuer. The minimum price for purchasing SR is determined by the government and has increased since 2009. Retail Sukuk are a form of investment for government assets. This study intends to examine the factors that influence the level for investor demand for the issuance of the SR-014 sukuk. The independent variables consist of sukuk yields, BI interest rates, ORI coupons and Islamic bank profit sharing. Retail Sukuk SR-014 was chosen as the dependent variable. The form of research to be conducted is a quantitative descriptive research. This study uses secondary data, and the analytical method used is multiple linear regression analysis which is processed using eviews software. The result of the research that has been carried out provides results, namely, the factor that affects the demand for retail sukuk SR-014, namely the yield of the sukuk itselfKeyword : Sukuk Price, Demand, Retail State Sukuk